2020
DOI: 10.1016/j.ijpharm.2019.118825
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and investigation of core-shell nanoparticles containing human interferon-α

Abstract: Sustained release of active interferon-α (IFN-α) has been achieved from core-shell nanoparticles (NPs) prepared by aqueous precipitation of IFN-α-enriched human serum albumin (HSA-IFN-α) and layer-by-layer (L-b-L) by coating of the IFN-α NPs with poly(sodium-4-styrene) sulphonate (PSS) and chitosan (Chit). The concentration and the pH of HSA solution were optimized during the development of this method. Dynamic light scattering (DLS), zeta-potential, thermal analysis (differential scanning calorimetry (DSC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Most importantly, the technique is usually conducted under normal experimental conditions and mainly in an aqueous solution, hence it is suitable to encapsulate proteins and polypeptide drugs [ 24 ], and recently the application of three layers of polyelectrolyte polymers in anticancer NPs demonstrated cancer-cell targeting with efficient internalization [ 25 ]. In our previous work NPs containing human interferon-α were formulated with the LBL approach by applying chitosan and polystyrene sulphonate [ 26 ]. The aim of our present work is to formulate, analyse and optimize core-shell type NPs containing LYS, as well as to write mathematical relationships between process parameters and product parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, the technique is usually conducted under normal experimental conditions and mainly in an aqueous solution, hence it is suitable to encapsulate proteins and polypeptide drugs [ 24 ], and recently the application of three layers of polyelectrolyte polymers in anticancer NPs demonstrated cancer-cell targeting with efficient internalization [ 25 ]. In our previous work NPs containing human interferon-α were formulated with the LBL approach by applying chitosan and polystyrene sulphonate [ 26 ]. The aim of our present work is to formulate, analyse and optimize core-shell type NPs containing LYS, as well as to write mathematical relationships between process parameters and product parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Kristó et al (2020) developed a nanoparticle with a core/shell structure, whose core was composed of IFN-α associated with human serum albumin, and the shell was constituted by three consecutive layers of polystyrene-chitosan-polystyrene sulfonate-sulfonate, respectively. This system exhibited sustained release for ten days without reducing cytokine biological activity in a higher organism ( Pannon rabbits) [ 152 ].…”
Section: Recent Encapsulation Forms Of Ifnsmentioning
confidence: 99%
“…In 2017, Cánepa et al synthesized chitosan nanoparticles that exhibited comparable antiviral activity to commercial IFNα in in vitro models.In the same study, preliminary in vivo assays in a CF1 mouse murine model showed that the molecule was detectable in the blood after one hour of oral administration of the formulation[109].Imperiale et al complemented this study in 2019 by demonstrating that the system provided bioavailability comparable to intravenously administered IFNα-2b in murine BALB/c mouse models[110].Kristó et al (2020) developed a nanoparticle with a core/shell structure, whose core was composed of IFNα associated with human serum albumin, and the shell was constituted by three consecutive layers of polystyrene-chitosanpolystyrene sulfonate-sulfonate, respectively. This system exhibited sustained release for ten days without reducing cytokine biological activity in a higher organism (Pannon rabbits)[111].IFNßFodor-Kardos et al in 2020 reported the first IFNß nanoencapsulation procedure. This research obtained nanometric particles with high encapsulation efficiency (>95%) to treat multiple sclerosis.…”
mentioning
confidence: 99%